Acute myelogenous leukemia - current recommendations and approaches in molecular-genetic assessment - Yahya Dinnar; Hachmeriyan Mari; Micheva Ilina; Chervenkov Trifon (Sciendo, 2022)
Acute myelogenous leukemia is a multi-step hematological malignancy, affecting function, growth, proliferation and cell cycle of myeloid precursors. Overall assessment of patients with the disease requires among everything else, a comprehensive investigation of the genetic basis through various methods such as cytogenetic and molecular-genetic ones. This clarification provides diagnostic refinement and carries prognostic and predictive value in respect of essential therapeutic choices.